1980
DOI: 10.3382/ps.0590598
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Phosphorus, Vitamin D3, and 25-Hydroxy Vitamin D3 Levels on Feed Intake, Productive Performance, and Egg and Shell Quality in Two Strains of Force-Molted White Leghorns

Abstract: A total of 576 force-molted hens were used to investigate the effect of dietary phosphorus level, and the source and level of vitamin D 3 on egg production and shell quality. The experiment was a 2 X 2 X 2 X 3 factorial design with two strains of hens, two levels of available phosphorus (.34 and .60%), and two sources of D 3 (25-hydroxy vitamin D 3 and vitamin D 3 ) at three levels (8, 16, 24 Mg/kg); the diets were provided ad libitum for 84 days (from 646 to 730 days of age). Egg and shell quality measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 17 publications
0
4
1
1
Order By: Relevance
“…However, in the present study, breeder hens failed to demonstrate improvements when 25 (OH)D 3 was added to feeds already containing 2,000 IU vitamin D 3 . Some results in the literature have produced similar outcomes such as those reported by Roland & Harms (1976), Abdulrahim et al (1978), Cohen et al (1978) and Hamilton (1980). An improved conversion into vitamin D is obtained when birds are fed 25 (OH) D 3 , therefore, supplementing breeder hen feeds with this compound was expected to improve eggshell quality (Soares et al, 1976).…”
Section: Resultsmentioning
confidence: 60%
“…However, in the present study, breeder hens failed to demonstrate improvements when 25 (OH)D 3 was added to feeds already containing 2,000 IU vitamin D 3 . Some results in the literature have produced similar outcomes such as those reported by Roland & Harms (1976), Abdulrahim et al (1978), Cohen et al (1978) and Hamilton (1980). An improved conversion into vitamin D is obtained when birds are fed 25 (OH) D 3 , therefore, supplementing breeder hen feeds with this compound was expected to improve eggshell quality (Soares et al, 1976).…”
Section: Resultsmentioning
confidence: 60%
“…On the other hand, Hamilton (1980) observed that D 3 promoted better egg production and feed conversion ratio (kg/kg) results relative to 25(OH) D 3 .…”
Section: Resultsmentioning
confidence: 91%
“…Esses resultados coincidem com os relatos de Hamilton (1980), que também não encontraram diferenças no consumo de ração, na produção e no peso de ovos ao trabalharem Médias seguidas de mesma letra maiúscula (linha) e minúscula (coluna) não diferem (p>0,05) entre si pelo teste Tukey.…”
Section: Resultsunclassified